Tracing Trends and Patterns of IKN Words in Media and Twitter: A Linguistic Corpus Study (Menelusuri Tren dan Pola Kata IKN di Media dan Twitter: Kajian Korpus Linguisti) - Devi Ambarwati Puspitasari; Kurniawan Kurniawan; Yenny Karlina; Hernina Hernina; Budi M Mulyo (Universitas PGRI Sumatera Barat, 2023)
This research focuses on the analysis of word trends and patterns associated with the